A case report : 34 y.o male with incidental histopathological findings of Kaposi sarcoma without clinical history of human immunodeficiency virus (HIV) (Research, Society and Development, 2023)
Introduction: Kaposi sarcoma is a rare and challenging case especially in immunosuppressed patients that frequently doesn’t have specific manifestation.  It usually caused by human herpes virus 8 virus infection and male patient with multiple lesion has high mortality rates. The aim of this study is to report 34 y.o Male with incidental histopathological findings of kaposi sarcoma without clinical history of Human Immunodeficiency Virus (HIV). Methodology: Descriptive study of the case report type, whose data were obtained from the patient's medical record. Result: This paper will report 34-year-old young adult male with clinically diagnosed with poroma and differential diagnosis of squamous cell carcinoma and pyogenic granuloma. The clinical sign was multiple skin lesion appear on his right nose and thumb in the last 6 months. The nodules are solitary with oval shape, erythema, firm borders and the nodule surface covered with brownish-yellow squama. In addition, imaging examination suspicious for soft tissue mass. The biopsy was performed, and histopathological finding exhibit a tumor mass consists of Kaposi sarcoma. Discussion: Furthermore, after pathological report revealed the diagnosis of Kaposi sarcoma then a provider-initiated HIV testing and counseling (PITC) examination is carried out and the test result showed reactive for HIV infection. So that, patient concluded to have predisposition of HIV infection with Kaposi sarcoma and treated for antiretrovirals (ARV), chemotherapy and routine clinical follow up. Conclusion :   Kaposi sarcoma is a rare cancer caused by infection with the human herpesvirus 8 (HHV8). These lesions are often found in immunosuppressed patients such as HIV sufferers characterized by vascular proliferation.  Through the incidental findings of Kaposi's sarcoma in patients who are not clinically suspected of having HIV, clinicopathological correlation is highly recommended. Therefore, the purpose of this writing can be a strong reference so that clinicians are more thorough in reviewing clinical patients and more detailed physical examinations.